Técnica de criação e parâmetros biológicos de Stegasta bosquella em amendoim - Boiça Junior, Arlindo Leal [UNESP]; Ribeiro, Zulene Antonio [UNESP]; de Campos, Aniele Pianoscki [UNESP]; Filho, Norton Rodrigues Chagas [UNESP] (My University, 2011)
Studies with Stegasta bosquella in peanut crop are little explored by researchers, mainly by the need of obtaining, in the field, a large quantity of closed leaflets. Therefore, it was sought a way of rearing in a natural diet that facilitates the attainment of the insect. The research was developed at the Laboratório de Resistência de Plantas a Insetos (FCAV/Jaboticabal) (T: 25 ± 2 °C, RH 60 ± 10% and photophase: 12 hours) (Runner IAC 886). The rearing stock of was carried out by collecting caterpillars from the field and keeping them in flat bottom glass tubes until adult emergence and test performance. Caterpillars were individualized in Petri dish plates, lined with moistened filter paper, which contained closed and early opened leaflets, but closed with paper clips (imitating the closed leaflet). A randomized design with two treatments and 36 repetitions was used. After the pupae formation, they were separated into five couples and the adults were kept in transparent plastic cages containing a peanut stem with leaves for oviposition, and fed with a 10% honey solution. The duration and viability of the larval and pupal periods, male and female longevity with and without food, and fertility were evaluated. The two forms of larvae rearing (closed leaflet and leaflet closed with clips) did not influence on any of the studied parameters. Therefore, the rearing of S. bosquella becomes feasible in natural diet, which means there is no need to use the enclosed leaflets for this purpose, and implies the easiness for rearing.
Rearing technique and evaluation of biological parameters of Stegasta bosquella in peanut
Keywords: Arachis hypogaea; Rearing methodology; Red-necked peanutworm